THE TITLES OF BOOKS DERIVED FROM POETRY: AN ANALYTICAL STUDY - Dr. Ansar Ahmed Shaikh (Zaban-o-Adab, 2022)
For any book the “TITLE” is an important point. Reader seeing the front page determines the value and worth of the book in his first glance. In the titles of Urdu books great advantage has been taken from the verse and words. It appears in the shape of compound, part and verse. There are compounds and constructions so abundant that this article could not bear the burden of them. In the article before sight we have included verse of proverbial poetry, part, or at least the TITLE of books consist of three words and their poetic credentials are ascertained from authentic and trustworthy editions and they are given with their help in the text with full accuracy. From this reference we have searched such books in abundance from Government and Private Libraries, P.D.F., Social Resources of Communications and Websites in which determining the titles of books verse and words are gleaned. In this process of seizing and obtainment of TITLES many immaturities, defects and flaws have been seen by us, so their Titles have been reviewed in this article from research and critical point of view.